The role of epigenetics in allergy and asthma development. Issue 1 (February 2020) - Alashkar Alhamwe, Bilal; Alhamdan, Fahd; Ruhl, Andreas; Potaczek, Daniel P.; Renz, Harald
Abstract : Purpose of review: Epigenetic mechanisms are known to play a crucial role in the pathogenesis of asthma, allergic rhinitis, atopic dermatitis, food allergy, and other allergic disorders, especially through mediating the effects of the environmental factors, well recognized allergy-risk modifiers. The aim of this work was to provide a concise but comprehensive review of the recent progress in the epigenetics of allergic diseases. Recent findings: Recent few years have substantially expanded our knowledge on the role of epigenetics in the pathogenesis and clinical picture of allergies. Specifically, it has been shown that epigenetic marks, especially DNA methylation, possess a diagnostic potential for atopic sensitization, asthma, allergic rhinitis, and food allergy. DNA methylation can be a predictor of clinical responses in controlled allergen challenges, including oral food challenges. Furthermore, direct or indirect targeting epigenetic mechanisms, this time especially histone modifications, was able to favorably affect expression of the genes underlying allergies and generally improve airway biology in allergic diseases or their animal models. Summary: Further studies are needed to explore the diagnostic and therapeutic potential of epigenetic modifications in allergies and to develop respective clinical tools. Abstract : Supplemental Digital Content is available in the text